Transition Metal Oxides for Organic Electronics: Energetics, Device Physics and Applications - Meyer, Jens; Hamwi, Sami; Kröger, Michael; Kowalsky, Wolfgang; Riedl, Thomas; Kahn, Antoine (Advanced materials (Weinheim), 2012)
During the last few years, transition metal oxides (TMO) such as molybdenum tri‐oxide (MoO3), vanadium pent‐oxide (V2O5) or tungsten tri‐oxide (WO3) have been extensively studied because of their exceptional electronic properties for charge injection and extraction in organic electronic devices. These unique properties have led to the performance enhancement of several types of devices and to a variety of novel applications. TMOs have been used to realize efficient and long‐term stable p‐type doping of wide band gap organic materials, charge‐generation junctions for stacked organic light emitting diodes (OLED), sputtering buffer layers for semi‐transparent devices, and organic photovoltaic (OPV) cells with improved charge extraction, enhanced power conversion efficiency and substantially improved long term stability. Energetics in general play a key role in advancing device structure and performance in organic electronics; however, the literature provides a very inconsistent picture of the electronic structure of TMOs and the resulting interpretation of their role as functional constituents in organic electronics. With this review we intend to clarify some of the existing misconceptions. An overview of TMO‐based device architectures ranging from transparent OLEDs to tandem OPV cells is also given. Various TMO film deposition methods are reviewed, addressing vacuum evaporation and recent approaches for solution‐based processing. The specific properties of the resulting materials and their role as functional layers in organic devices are discussed. Various transition metal oxides such as molybdenum oxide (MoO3), vanadium oxide (V2O5), and tungsten oxide (WO3) are reviewed; from fundamental analysis to advanced device applications for organic electronics.